Avaliação in vitro do potencial antimicrobiano do óleo essencial de Hyptis pectinata (L.) Poit. e de colutórios sobre os Streptococcus mutans - Nascimento, Paula Frassinetti Coelho (2005)
The modern dentistry emphasizes the importance of the control of the dental biofilm to improve the oral health. The use in the odontologic therapeutics rinses has a crucial paper in the reduction of the biofilm. The effectiveness of these substances was appraised extensively in several studies. The pharmacologic research of medicinal plants is necessary due to its therapeutic capacity and use. Essential oils and extracts of plants have been used for several applications in the popular medicine, among them as antimicrobial and antiseptic topics. There are several methods described inside the literature for size the antimicrobial activity of the essential oils. However the measure of this activity is hindered by the absence of standardized methods, what dificults the comparison among the studies. Besides, disables its reproduction. The present work researched in vitro the susceptibility of Streptococcus mutans to the Hyptis pectinata essential oil. It presents antimicrobial activity equivalent to the chlorhexidine, what demonstrates the use of this oil as promising alternative in the regiments of oral health. Validating the antimicrobial properties of the Hyptis pectinata essential oil, an experiment was developed using the diffusion technique in disk with some variations in the diluents of the oil, among them Tween 20 and Tween 80 are the most suitable for the emulsification of the Hyptis pectinata oil. The obtained data emphasize a considerable interest for the development of reliable methods for evaluation and comparison of the activity antimicrobial of essential oils.